Comparative Inhibitory Effects of Natural Biflavones from Ginkgo against Human CYP1B1 in Recombinant Enzymes and MCF-7 Cells - Chen, Xiaodong; Zhao, Tingting; Du, Jie; Guan, Xintong; Yu, Hong; Wang, Dalong; Wang, Changyuan; Meng, Qiang; Yao, Jialin; Sun, Huijun; Liu, Kexin; Wu, Jingjing (Planta Medica, 2022)
Human cytochrome P450 1B1 (CYP1B1) is an extrahepatic enzyme overexpressed in many tumors and associated with angiogenesis. Ginkgetin, isoginkgetin, sciadopitysin, and amentoflavone, the primary biflavones found in Ginkgo biloba, have excellent anti-inflammatory and anti-tumor effects. However, the effect of biflavones on CYP1B1 activities remains unknown. In this study, 7-ethoxyresorufin O-deethylation (EROD) was used to characterize the activities of CYP1 families. The impacts of four ginkgo biflavones on CYP1B1 activity and the cellular protein expression of CYP1B1 were systematically investigated. The results showed that amentoflavone with six hydroxyl substituents exhibited the most potent selective inhibitory effect on CYP1B1 activity with IC50 of 0.054 µM in four biflavones. Sciadopitysin, with three hydroxyl and three methoxy substituents, had the weakest inhibitory activity against CYP1B1. Ginkgetin and isoginkgetin, both with four hydroxyl and two methoxy substituents, showed similar inhibitory intensity towards CYP1B1 with IC50 values of 0.289 and 0.211 µM, respectively. Kinetic analysis showed that ginkgetin and amentoflavone inhibited CYP1B1 in a non-competitive mode, whereas sciadopitysin and isoginkgetin induced competitive or mixed types of inhibition. Notably, four ginkgo biflavones were also confirmed to suppress the protein expressions of CYP1B1 and AhR in MCF-7. Furthermore, molecular docking studies indicated more hydrogen bonds formed between amentoflavone and CYP1B1, which might explain the strongest inhibitory action towards CYP1B1. In summary, these findings suggested that biflavones remarkably inhibited both the activity and protein expression of CYP1B1 and the inhibitory activities enhanced with the increasing hydroxyl substitution, providing new insights into the anti-tumor potentials of biflavones.
Keywords: CYP1B1; Ginkgo biloba; biflavones; inhibition; AhR; structure-inhibition relationship